ANALISIS SPASIAL TINGKAT BAHAYA EROSI DI DAERAH ALIRAN SUNGAI (DAS) MORAMO DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) - Tufaila, Muh.; Karim, Jufri; Alam, Syamsu (Jurnal Agroteknos, 2012)
Spatial analysis on erosion potential is required to create an integrated management of watersheds, thoroughly and, environmentally sustainable, where the watershed as a management unit. The research was conducted in the watershed area Moramo South Konawe. This research was conducted through an overlay approach using geographic information system (GIS) map of Thiessen polygons, slope maps, soil maps and land use maps. The study obtained five classes of erosion potential, namely very light (2685.60 ha or 21.27 %); light (2359.08 ha or 18.68 %); medium (903.70 ha or 7.16%); heavy ( 381.63 hectares or 3.02% ) ; and very heavy 6297.94 hectares or 49.87 %). Dominant erosion hazard level in the basin Moramo was in the District Moramo, approximately 3496.75 hectares or 27.69 % of the total area of the watershed Moramo and had been used for agricultural land for approximately 3992.48 hectares or 31.62 %. Keywords : Erosion, GIS, Moramo, Watershead Management,